(untitled) (Indian Journal of Veterinary Pathology, 2026)
Feline Panleukopenia Virus (FPV) is a highly contagious viral disease causing severe hematological abnormalities in cats. This study was aimed to evaluate the hematological, biochemical, and bone marrow changes in naturally infected cats and to characterize FPV at the molecular level. A total of 22 cats exhibiting clinical signs of anorexia, pallor of mucus membrane, recumbency, and emaciation were examined. Out of this 7 were subjected to detailed post-mortem evaluation. Hematological analysis revealed significant anemia, leukopenia, and thrombocytopenia in FPV-infected cats, accompanied by hypoglycemia and hypoproteinemia, while liver and kidney parameters remained largely unaffected. Blood smear and bone marrow cytology showed predominant erythroid hypoplasia, myeloid hypoplasia and megakaryocytic hyperplasia, indicating compensatory hematopoietic responses. Necropsy findings included generalized pallor of visceral organs, thickened intestines with mucosal petechiae, mild hepatomegaly, and pulmonary edema. Molecular detection of DNA of FPV from 19 bone marrow samples via PCR targeting the VP2 gene confirmed infection in 15 cats (78.95%). Phylogenetic analysis revealed that the Indian bone marrow isolate clustered closely with other Indian FPV strains, forming a distinct clade separated from strains reported in Europe, Africa, and East Asia, suggesting geographic evolution patterns. These findings highlight the critical role of bone marrow in FPV pathogenesis, the systemic impact of infection, and the regional genetic distinctness of circulating FPV strains in India, which has implications for disease surveillance and vaccine strategies.